2012
DOI: 10.3329/bjch.v36i2.13085
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Tract Infection in Children: An Update

Abstract: Background: A large number of children with Urinary Tract Infection (UTI) are seen in the community by general practitioners , but there is frequently delay in treatment and not all are referred for further investigations. There is evidence that many cases are misdiagnosed. It is important to optimize diagnostic and management strategies. Result: UTI is an important cause of acute illness, it may be a marker of underlying urinary tract abnormality. Bacteria causes the large majority of UTI in children- Escheri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 17 publications
2
12
0
Order By: Relevance
“…5 Urine culture & sensitivity is the gold standard for the diagnosis of UTI. 6 On culture, a colony count of more than 10 5 colony forming units /ml organisms of a single species in midstream urine of girls and >10 4 CFU/ml organisms in boys are considered confirmatory of UTI. 7 A pure growth of ≥10 2 CFU/ml from catheterized urine sample or growth of any number of uropathogen from urine obtained by suprapubic aspiration is considered as significant bacteriuria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Urine culture & sensitivity is the gold standard for the diagnosis of UTI. 6 On culture, a colony count of more than 10 5 colony forming units /ml organisms of a single species in midstream urine of girls and >10 4 CFU/ml organisms in boys are considered confirmatory of UTI. 7 A pure growth of ≥10 2 CFU/ml from catheterized urine sample or growth of any number of uropathogen from urine obtained by suprapubic aspiration is considered as significant bacteriuria.…”
Section: Introductionmentioning
confidence: 99%
“…7 A pure growth of ≥10 2 CFU/ml from catheterized urine sample or growth of any number of uropathogen from urine obtained by suprapubic aspiration is considered as significant bacteriuria. 5 Although E. coli has been reported to account for most of the cases of symptomatic UTI in children, 6,7 studies from some other parts of the world however, have shown a changing trend in the bacteriology of UTI. [8][9][10] The spectrum of etiologic agents causing UTI and their antimicrobial resistance pattern have been continuously changing over the years, both in community and in hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…e potential risk factors for UTI around the world were selected from different studies. [1][2][3][4][5][6][7][8][9][10][11][12] en, a sample of 20 questionnaire were conducted in early January as field test to only keep ten effective variables related to the study area (Dhaka). e questionnaire was designed with both open-ended (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies 8,9,10 have been recently conducted in Bangladesh for UTI in children, however, those studies are either conduct a review or diagnosis of UTI from medical perspective. is study however, undertook to identify and measure magnitude of the potential risk factors of UTI in hospitalized children less than 5 years of age in Bangladesh using observational and statistical approach comparing cases against control groups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation